Critical Appraisal of Macitentan in Pulmonary Arterial Hypertension - Dewi IP., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Critical Appraisal of Macitentan in Pulmonary Arterial Hypertension